2008
DOI: 10.1248/bpb.31.316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Severity Disease on the Pharmacokinetics of Cefuroxime in Children with Multiple Organ System Failure

Abstract: The aim of the present study was to investigate if the severity of illness affected the pharmacokinetics of cefuroxime in 11 children diagnosed with multiple organ system failure. The patients were assigned to a severely ill group (group 1), a very severely ill group (group 2), or a control group (group 0). Blood samples were taken and cefuroxime concentrations were measured in plasma by HPLC after the first intravenous infusion of 100 mg of cefuroxime per kg of body weight. The pharmacokinetic profile of cefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Therefore, the identification of these concentrations is of paramount importance if we want to get the maximum therapeutic benefit. The results of the present study suggest a modification in the treatment regimens in Neonatology service of General Hospital of Durango, Mexico, as was recommended in previous studies [27, 28]. …”
Section: Discussionsupporting
confidence: 69%
“…Therefore, the identification of these concentrations is of paramount importance if we want to get the maximum therapeutic benefit. The results of the present study suggest a modification in the treatment regimens in Neonatology service of General Hospital of Durango, Mexico, as was recommended in previous studies [27, 28]. …”
Section: Discussionsupporting
confidence: 69%
“…We identified only one study on cefuroxime PK in PICU patients [30], 15 patients in total, including 4 non-critically ill patients with pharyngitis. The 11 PICU patients were divided in 2 groups: a severely ill group of 5 PICU patients not requiring mechanical ventilation, and a very severely ill group with 6 patients requiring mechanical ventilation.…”
Section: Cefuroximementioning
confidence: 99%
“…A total of twenty studies were reported among pediatrics ( Table 1 ). Of 20 studies, eight studies were reported on penicillins ( Cies et al, 2014 ; De Cock et al, 2015 ; Nichols et al, 2016 ; De Cock et al, 2017 ; Béranger et al, 2019 ; Tang et al, 2019 ; D’Agate et al, 2020 ; Wu et al, 2021 ), eight on cephalosporins ( Olguin et al, 2008 ; Fukumoto et al, 2009 ; De Cock et al, 2016 ; Cies et al, 2018a ; Béranger et al, 2018 ; Cies et al, 2019 ; Hartman et al, 2019 ) and 4 on carbapenems ( Giannoni et al, 2006 ; Cies et al, 2015 ; Cies et al, 2017b ; Tan et al, 2018 ) ( Table 1 ). Four studies were reported on amoxicillin ( De Cock et al, 2015 ; Tang et al, 2019 ; D’Agate et al, 2020 ; Wu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The recommended dose of cefotaxime ranges from 100 mg to 300 mg/kg as a continuous infusion that achieved 100% probability target attainment (PTA). Olguin et al (2008) studied the PK parameters of cefuroxime on 11 patients with septicemia and septic shock. The authors recommended the dose of 100 mg/kg of body weight, administered every 6 h by intravenous infusion for 30 min.…”
Section: Resultsmentioning
confidence: 99%